Utilization of a Ride-Share Application and Patient Navigation Program for Promoting Colonoscopy Among High-Risk Adults - Zumana Miyfa; Lisa Ho; Vladimir Khristov; Maryknoll Palisoc; Hannah Bennett; Siddhartha Roy; Thomas McGarrity; Megan Mendez-Miller (Journal of Student-Run Clinics, 2022)
Colonoscopy screening starting at age 50 is key for the early detection and prevention of colorectal cancer (CRC). Barriers to care, such as lack of insurance, transportation, and healthcare literacy, can deter a patient from completing a screening colonoscopy. Delayed CRC screening results in missed opportunities for detecting disease at an earlier stage, ultimately leading to increased healthcare costs and morbidity. We implemented a pilot program that combines student-led patient navigation with ride-share services to promote colonoscopy screening among at-risk populations in Harrisburg, Pennsylvania, United States, at no cost to patients. During the first year of the program, the rate of adequate colonoscopy preparation was 77% (10 out of 13 patients), and the attendance rate was 100% for all scheduled appointments. While this study analyzed a small cohort of participants, it demonstrates how a colonoscopy screening program can be organized and conducted successfully through collaboration among multiple stakeholders. Future aims include expanding the program and assessing its receptiveness via post-procedure surveys for patients, patient navigators, and healthcare providers.